Physiological protective action of dissolved organic carbon on ion regulation and nitrogenous waste excretion of zebrafish (Danio rerio) exposed to low pH in ion-poor water - Duarte, Rafael M. [UNESP]; Wood, Chris M.; Val, Adalberto L.; Smith, D. Scott (Springer Nature, 2018)
Dissolved organic carbon (DOC) represents a heterogeneous group of naturally-occurring molecules in aquatic environments, and recent studies have evidenced that optically dark DOCs can exert some positive effects on ionoregulatory homeostasis of aquatic organisms in acidic waters. We investigated the effects of Luther Marsh DOC, a dark allochthonous DOC, on ion regulation and N-waste excretion of zebrafish acutely exposed to either neutral or low pH in ion-poor water. In the first experiment, simultaneous exposure to pH 4.0 and DOC greatly attenuated the stimulation of Na+ diffusive losses (Jout Na), and prevented the blockade of Na+ uptake (Jin Na) seen in zebrafish exposed to pH 4.0 alone, resulting in much smaller disturbances in Na+ net losses (Jnet Na). DOC also attenuated the stimulation of net Cl− losses (Jnet Cl) and ammonia excretion (Jnet Amm) during acidic challenge. In the second experiment, zebrafish acclimated to DOC displayed similar regulation of Jin Na and Jout Na, and, therefore, reduced Jnet Na at pH 4.0, effects which persisted even when DOC was no longer present. Protective effects of prior acclimation to DOC on Jnet Cl and Jnet Amm at pH 4.0 also occurred, but were less marked than those on Na+ balance. Urea fluxes were unaffected by the experimental treatments. Overall, these effects were clearly beneficial to the ionoregulatory homeostasis of zebrafish at low pH, and were quite similar to those seen in a recent parallel study using darker DOC from the upper Rio Negro. This suggests that dark allochthonous DOCs share some chemical properties that render fish tolerant to ionoregulatory disturbances during acidic challenge.
Keywords: Allochthonous DOC; Ammonia excretion; Chloride net fluxes; Na+ uptake; Natural organic matter; Paracellular Na+ losses